Using circuit theory, connectivity analysis and least-cost path to model the potential ecological corridors of Malayan Tapir (Tapirus indicus) at Chini-Bera Forest Complex in Pahang, Peninsular Malaysia - Amal Najihah Muhamad Nor,; Nur Hairunnisa Rafaai,; Saiful Arif Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2023)
In Peninsular Malaysia, the Master Plan of Ecological Linkages has proposed ecological corridors at Chini-Bera forests complex to connect the forest patches. However, the proposed corridors have been determined arbitrarily without evaluating the reliability of the landscape structure which may cause liability in conservation effort. Therefore, the objective of this study was to determine the potential ecological corridors by considering the reliability of landscape structure in Chini-Bera forests complex using Malayan tapir (Tapirus indicus) as a focal species. The tapir was chosen because it is one of the target large mammals in the master plan. In this study, three landscape structures, i.e., patch size, patch distance and landscape resistance were used as parameters in modelling the potential ecological corridors for tapirs. In the modelling, circuit theory, connectivity analysis and least-cost path were integrated using the geographic information systems and remote sensing platforms. The model has identified a total of 35 potential ecological corridors for tapir of which over 50% connect the large core areas while the other 25% connect the small core areas. Meanwhile, four corridors can be considered as priority corridor as their effective resistance below 1000 which indicate easy movement and high connectivity. The findings showed the importance to consider the reliability of the patch size, patch distance dan landscape resistance in determining the potential ecological corridors of wildlife to avoid liability in conservation effort. In addition, the integrated modelling approach contributes to a more concrete assessment of ecological corridors for effective wildlife conservation planning.